Advances in HIV/AIDS treatment - Schechter, Mauro (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Iwould Uke to thank the Conference Organizers for giving me the honor and privilege of presenting this talk to sucb a distinguished audience. [...]